1995
DOI: 10.1212/wnl.45.3.544
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Encephalomyelitis Antigens Bind to the AU-rich Elements of mRNA

Abstract: The Hu antigens are composed of a family of neuronal-specific, RNA-binding proteins encoded by at least three distinct genes. All three gene products, HuD, HuC/ple21, and Hel-N1, are human homologues of Elav, a Drosophila protein required for neuronal development and maintenance. Although the three proteins are very similar in structure, they are differentiated by alternative splicing of their mRNAs. We report here that the Hu antigens bind avidly to the AU-rich element resident in many mRNAs that regulate cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
0
3

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 14 publications
6
88
0
3
Order By: Relevance
“…It encodes the most common isoform, HuD, lacking the second alternate exon in the hinge domain (amino acid residues 252 to 265) (30) and carries C-terminal hexahistidine and MYC epitope tags. The HuB expression plasmid (pET3d-Hel-N1, F622) contains the same epitope tags as F578 and was derived by PCR from plasmid pCMVHel-N1 (kindly provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…It encodes the most common isoform, HuD, lacking the second alternate exon in the hinge domain (amino acid residues 252 to 265) (30) and carries C-terminal hexahistidine and MYC epitope tags. The HuB expression plasmid (pET3d-Hel-N1, F622) contains the same epitope tags as F578 and was derived by PCR from plasmid pCMVHel-N1 (kindly provided by Drs.…”
Section: Methodsmentioning
confidence: 99%
“…Members of the embryonic lethal abnormal vision (ELAV) family of proteins have been shown to bind with high affinity to AREs within the 3Ј-UTR of mRNAs of genes involved in cellular growth and neuronal differentiation (20,(33)(34)(35)(36)(37). The functional significance of the interactions between AREs and ELAV proteins has been investigated, and a number of studies have demonstrated that ELAV proteins inhibit ARE-mediated mRNA turnover (28, 31, 33, 38 -41).…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%
“…At least 14 apparently distinct AREbinding proteins have been identified in eukaryotic cell extracts by UV-cross-linking and gel shift assays (reviewed in Ref. 26), and there is evidence indicating that binding of these trans-acting factors to AREs influences mRNA degradation (27)(28)(29)(30)(31)(32).Members of the embryonic lethal abnormal vision (ELAV) family of proteins have been shown to bind with high affinity to AREs within the 3Ј-UTR of mRNAs of genes involved in cellular growth and neuronal differentiation (20,(33)(34)(35)(36)(37). The functional significance of the interactions between AREs and ELAV proteins has been investigated, and a number of studies have demonstrated that ELAV proteins inhibit ARE-mediated mRNA turnover (28, 31, 33, 38 -41).…”
mentioning
confidence: 99%
“…To characterize the m-Msi-1-expressing cells in this region, double-label indirect immunostaining was performed with antibodies to m-Msi-1 and to a cell-type specific marker protein, including the Hu proteins HuD (Szabo et al, 1991), HuC (Liu et al, 1995), and HelN-1 (Levine et al, 1993), which label immature and differentiated neurons, C N Pase for myelinating and nonmyelinating differentiated oligodendrocytes (Sprinkle, 1989), and GFAP for astrocytes. GFAP is an intermediate filament that is specifically expressed in mature astrocytes (Bignami and Dahl, 1974).…”
Section: M-msi-1 Expression In the Svz Of The Forebrainmentioning
confidence: 99%